Optimised Extraction of Trypsin Inhibitors from Defatted Gac (Momordica cochinchinensis Spreng) Seeds for Production of a Trypsin Inhibitor-Enriched Freeze Dried Powder - Anh V. Le; Sophie E. Parks; Minh H. Nguyen; Paul D. Roach (Separations, 2019)
The seeds of the Gac fruit, Momordica cochinchinensis Spreng, are rich in trypsin inhibitors (TIs) but their optimal extraction and the effects of freeze drying are not established. This study aims to (1) compare aqueous solvents (DI water, 0.1 M NaCl, 0.02 M NaOH and ACN)/water/FA, 25:24:1) for extracting TIs from defatted Gac seed kernel powder, (2) to optimise the extraction in terms of solvent, time and material to solvent ratio and (3) to produce a TI-enriched freeze-dried powder (FD-TIP) with good characteristics. Based on the specific TI activity (TIA), the optimal extraction was 1 h using a ratio of 2.0 g of defatted powder in 30 mL of 0.05 M NaCl. The optimisation improved the TIA and specific TIA by 8% and 13%, respectively. The FD-TIP had a high specific TIA (1.57 ± 0.17 mg trypsin/mg protein), although it also contained saponins (43.6 ± 2.3 mg AE/g) and phenolics (10.5 ± 0.3 mg GAE/g). The FD-TIP was likely stable during storage due to its very low moisture content (0.43 ± 0.08%) and water activity (0.18 ± 0.07) and its ability to be easily reconstituted in water due to its high solubility index (92.4 ± 1.5%). Therefore, the optimal conditions for the extraction of TIs from defatted Gac seed kernel powder followed by freeze drying gave a high quality powder in terms of its highly specific TIA and physical properties.